2007
DOI: 10.1007/s11661-007-9273-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermetallic Phases on the Bond Strength of Diffusion-Bonded Joints between Titanium and 304 Stainless Steel Using Nickel Interlayer

Abstract: Solid-state diffusion bonding was used to join commercially pure titanium (Ti) and 304 stainless steel (SS) with a pure nickel (Ni) interlayer of 300-lm thickness in the temperature range of 800°C to 950°C in steps of 50°C for 7.2 ks under 3 MPa load in vacuum. Interfaces were characterized using light and scanning electron microscopy. The interdiffusion of the chemical species across the diffusion interfaces was evaluated by electron probe microanalysis. Nickel interlayer completely restricted the migration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…In contrast, Taguchi et al [18] have reported a high value of 360 kJ mol -1 for growth of bTi(Fe) phase during annealing in the temperature range of 677-867°C. Hence, it is obvious from literature that the presence of intermetallic phases and secondary phases at the interface control the overall growth of the reaction zones [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Taguchi et al [18] have reported a high value of 360 kJ mol -1 for growth of bTi(Fe) phase during annealing in the temperature range of 677-867°C. Hence, it is obvious from literature that the presence of intermetallic phases and secondary phases at the interface control the overall growth of the reaction zones [19].…”
Section: Introductionmentioning
confidence: 99%
“…The Ti-intermetallics interface is characterised by the presence of a light-shaded reaction zone containing β-Ti and the Widmanstätten α-β-Ti structure. The migration of copper atoms to titanium lattice lowers the eutectoid transformation temperature of titanium since copper is a strong β-stabilising element [25]. During cooling, α-β-phase aggregate forms due to the decomposition of β-Ti.…”
Section: Microstructurementioning
confidence: 99%
“…Для преодоления этой проблемы S. Kundu с соавторами предложили ис-пользовать никелевую прослойку [11][12][13][14]. Были иссле-дованы соединения с нержавеющей сталью как техни-чески чистого титана [11][12][13], так и сплава типа ВТ6 [14], при этом авторы использовали никелевую про-слойку с крупнозернистой микроструктурой.…”
Section: Introductionunclassified